Festkorper Probleme VIII : in Referaten des Fachausschusses "Halbleiter" der Deutschen Physikalischen Gesellschaft, Berlin 1968 : zugleich Hauptvortrage des Fachausschusses "Tiefe Temperaturen" des Fachausschusses "Thermodynamik und statistiche Mechanik" und der Arbeitsgemeinschaft "Metallphysik" - Madelung, O. (Otfried) (Pergamon Press, 1968)
Festkorper Probleme VIII reviews the status of radiation damage in semiconducting materials and components. This book examines the problems connected to the mechanism of production of defects by bombardment with energetic particles, particularly the displacement energy. Comprised of nine chapters, this book begins with an overview of the microstructure of radiation defects in silicon, which is known from optical absorption experiments and electron spin resonance. This text then explains the preparation of single crystals of high purity or defined impurity contents, which is the basis of succes.